Evaluation of Eluxadoline Effect on Cardiac Repolarization. Issue 7 (16th April 2018) - Bonifacio, Laura; Hunt, Thomas L.; McIntyre, Gail; Dove, Leonard S.; Covington, Paul S.
Abstract: This study evaluated the effects of eluxadoline, a mixed μ‐opioid receptor (OR) and κ‐OR agonist and δ‐OR antagonist, on cardiac repolarization. This evaluator‐blinded, placebo‐ and positive‐controlled, 4‐period crossover study randomized healthy men and women to single oral doses of eluxadoline (therapeutic dose 100 mg or supratherapeutic dose 1000 mg), moxifloxacin 400 mg, or placebo. QT data were corrected using individual custom correction (QTcI). The primary endpoint was the change from baseline in QTcI intervals (ΔQTcI) between eluxadoline and placebo (ΔΔQTcI). An upper bound of the 95% confidence interval around ΔΔQTcI of 10 milliseconds was considered clinically significant. Concentration–QTc data were analyzed using a repeated‐measures, mixed‐effects linear model. Sixty‐four volunteers were treated, and 58 completed the study. Assay sensitivity was demonstrated with moxifloxacin (noted by ΔΔQTcI of 11.94 milliseconds). The maximum ΔΔQTcI for eluxadoline 1000 mg was 4.10 milliseconds 1 hour postdose (1‐sided 95% upper confidence bound, 5.81 milliseconds), and for eluxadoline 100 mg was 1.20 milliseconds at 0.5 hours postdose (1‐sided 95% upper confidence bound, 2.91 milliseconds). Primary ΔΔQTcI results were confirmed using Fridericia's formula for QTc. Categorical, morphological, and concentration–QTc analyses were consistent with the primary and secondary findings. There were no significant gender effects on ΔΔQTcI values. The most common adverse events were contact dermatitis and nausea (12.5% each) and dizziness (10.9%); adverse events were more frequent in the eluxadoline 1000 mg group. In conclusion, eluxadoline, at therapeutic or supratherapeutic doses, did not significantly prolong QT intervals, and was safe and generally well tolerated in this study population.